1986
DOI: 10.3168/jds.s0022-0302(86)80573-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steroidal Sapogenins on Ruminal Fermentation and on Production of Lactating Dairy Cows

Abstract: Supplementation of dairy rations with steroidal sapogenins was evaluated in an in vitro, an in situ, and a production trial. Sixteen in vitro semicontinuous rumen cultures were supplied a 55:45 concentrate to roughage substrate with Sarsaponin concentrations of 0, 33, 55, and 77 ppm of air-dry feed for 22 d. Supplementation decreased protozoa numbers and increased bacterial numbers and acid detergent fiber digestion. Digestion of feed nitrogen tended to be lowest at the highest concentration of Sarsaponin, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
64
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 13 publications
18
64
0
2
Order By: Relevance
“…Conversely, Hussain & Cheeke (41) found a numerically lower propionate concentration in vivo with 75 ppm of Yucca saponins. However, Valdez et al (29) and Wu et al (40) did not observe a significant change in propionate concentration in vivo up to 77 and 125 ppm, respectively, of Yucca saponins. The responses of saponins on rumen VFA production are often diet dependent.…”
Section: Digestion Of Feeds and Volatile Fatty Acid Productionmentioning
confidence: 98%
See 4 more Smart Citations
“…Conversely, Hussain & Cheeke (41) found a numerically lower propionate concentration in vivo with 75 ppm of Yucca saponins. However, Valdez et al (29) and Wu et al (40) did not observe a significant change in propionate concentration in vivo up to 77 and 125 ppm, respectively, of Yucca saponins. The responses of saponins on rumen VFA production are often diet dependent.…”
Section: Digestion Of Feeds and Volatile Fatty Acid Productionmentioning
confidence: 98%
“…One of the earliest observations was made by Valdez et al (29) who showed that a commercial sarsaponin (steroidal spirostanol saponin) extracted from the Yucca schidigera plant decreased the protozoal population with a small increase in bacterial numbers in continuous culture systems. In many subsequent studies, the extracts of Y. schidigera have been shown to suppress the growth of rumen protozoa in vitro (44) without affecting DM disappearance and other rumen microbial populations (45) .…”
Section: Ciliate Protozoamentioning
confidence: 99%
See 3 more Smart Citations